2021
DOI: 10.3390/pr9030520
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Moisture and Temperature to the Concentration of O2 and CO2 during Biodrying in Semi-Static Piles

Abstract: Biodrying was studied over 46 days in two piles (P1 and P2) composed of orange peel and two structuring materials (mulch: P1; sugarcane bagasse: P2). The oxygen and carbon dioxide levels were recorded at different depths (0.1 to 0.6 m). From the beginning to days 33–35 the drying was carried out by a combination of microbial heat, convection, and solar irradiance; moisture reached 30%, corresponding to a water activity (aw) of 0.88–0.9, which was insufficient to maintain microbial activity. Additionally, the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Biochar improves aeration (due to its high nano-porosity and large surface area) [ 61 ] and also increases the activity of microorganisms in the composting process [ 60 ]. Contreras-Cisneros et al [ 62 ] and Wei et al [ 63 ] have reported that the positive effect of biochar on the biological treatment of waste is also related to the ability of the biochar to bind water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Biochar improves aeration (due to its high nano-porosity and large surface area) [ 61 ] and also increases the activity of microorganisms in the composting process [ 60 ]. Contreras-Cisneros et al [ 62 ] and Wei et al [ 63 ] have reported that the positive effect of biochar on the biological treatment of waste is also related to the ability of the biochar to bind water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The temperature in the biodrying process is in the range of 28.4-34.1C. This was done following several previous studies using a range of 30-40°C [13,14]. The variations used in this biodrying research was shown in Table 1 and the image of vegetable waste used in this work was displayed in Figure 1.…”
Section: Time and Locationmentioning
confidence: 99%
“…The water removal is supported by both the heat produced by the microorganisms in the biodegradation processes and the air ventilation system. The biodrying process is considered a good solution for a quick reduction in the water content of the MSW [11][12][13][14]. The method has the versatile possibilities of using the product of the treatment because it allows one to achieve the required moisture reduction, the volume reduction, and the bulk density enhancement through the effective utilization of the biological heat [11,15,16].…”
Section: Introductionmentioning
confidence: 99%